Essays on a priori knowledge and justification - Casullo, Albert (Oxford : Oxford University Press, 2012)
Provides an important historical record of the development of investigations into the a priori during a critical period in which it emerged from being a rather arcane topic in the epistemological literature to occupying a central role.
Includes bibliographical references.
Description based on print version record.
Keywords: A priori